Pemanfaatan Teknologi Informasi dan Pengendalian Internal Terhadap Ketepatwaktuan Pelaporan Keuangan pada Dinas Pemerintah Kota Makassar - Sahidah; Rinaldy, Syiar (Insan Cita Bongaya Research Journal, 2024)
This study aims to determine whether the Use of Information Technology and Internal Control affect the Timeliness of Financial Reporting. This study belongs to quantitative research. The population consisted of employee in financial sub division in Makassar City Government Office with the total number of 124 employee. The sample was determined by saturated sample. Then the respondents in this research were 124 people. The data collection technique was questionnaire. The data analysis used multiple regression.The result showed that use of Information Technology had a positive and not significant effect on The Timeliness of Financial Reporting, internal controls had a positive and significant effect on The Timeliness of Financial Reporting, and simultaneously the Use of Information Technology and Internal Controls had a positive and significant effect on The Timeliness of Financial Reporting.